KONSEP PERANCANGAN BERBASIS ARSITEKTUR LOKAL: (STUDI KASUS: DESAIN FASILITAS PENUNJANG PAGELARAN BUDAYA DI DESA BAHA, BALI) - I Putu Surya Mitra; I Wayan Parwata; I Wayan Widanan (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2020)
Planning and Design of Supporting Facilities for Cultural Performance The Tourism Village aims to optimize the Tourism Village in Baha Village can be better than before. The effort to create a Supporting Facility for Cultural Tourism Village in Baha Village which is later expected to be able to develop or improve the quality and function of various existing potentials, from the many potentials owned by Baha village, then an idea arises to further enhance and strengthen the existence of a tourist village in the village This Baha with a planning and design which later can become a place of tourism based on the existing potential. So the concept or idea for this problem is the Cultural Performance Support Facility that can support the potential possessed to advance the tourist village. So that in the planning and Design of Support Facilities for the Cultural Performance of the Tourism Village there will be a tour package with nuances of nature, art, culture, history, and spirituality. Keywords: Baha Tourism Village; Desain Concepts; Local Architecture